Factors that motivates brand loyalty within the airline services industry – Aspects from behavioral loyalty and attitudinal loyalty - Chan, Kok Hoe (2011)
Often we seen organizations from all industries fighting for survival in today’s intense market place, and airline service industry is no exception. Such dynamic challenges placed brand loyal customers as an important asset to maintain an airline’s success. Therefore, this thesis observes and ascertains the motivators of brand loyalty towards the airline services industry. Relevant studies and previous research are integrated to present a theoretical framework of brand loyalty in the airline service industry in particular. It is analyzed that brand loyalty here, have two different approaches; behavioral loyalty and attitudinal loyalty. Four motivating factors are then identified; switching cost to competitors’ airline, flight crew service quality, trustworthiness of the airline companies, and social identity provided by the airline companies. A quota sampling methodology, targeting 200 respondents of different background is carried out. Responses collected revealed the strength of the determining factors when purchasing an airline service. Accordingly, this thesis relates the main essence of sustaining brand loyalty, hence, creating a competitive winning edge of airline companies. At the end of this paper, the research finding reveals that both behavioral loyalty and attitudinal loyalty can work together in order to create high brand loyalty. However, among the four identified and tested independent variables, trustworthiness of airline companies and flight crew service quality, each from the two different dimension of brand loyalty were seen proven significant in the results towards the dependent variables. With that, the researcher came to conclude that trustworthiness of airline companies and flight crew service quality, both play major roles in creating and enhancing high brand loyalty.